Insights for Canadian electricity generation planning from an integrated assessment model: Should we be more cautious about hydropower cost overruns?. (March 2021) - Arbuckle, Evan J.; Binsted, Matthew; Davies, Evan G.R.; Chiappori, Diego V.; Bergero, Candelaria; Siddiqui, Muhammad-Shahid; Roney, Christopher; McJeon, Haewon C.; Zhou, Yuyu; Macaluso, Nick
Abstract: Hydropower accounts for approximately 60% of electricity generation in Canada, with growth expected in the coming decades as part of renewable energy transitions; however, frequent cost overruns threaten the viability of this growth. Using the integrated assessment model GCAM, we develop an endogenous representation of hydropower for Canada that accounts for market dynamics, thus permitting analysis of hydropower competition with other electricity generation technologies, both with and without cost overruns. Results show that modelling hydropower resources endogenously increases Canadian hydropower deployment relative to an assumption of fixed hydropower production, from 417 to 495 TWh annually by 2050. In scenarios that apply cost overruns at historical levels, hydropower loses market share to more easily scalable technologies like wind power. When including high cost overrun assumptions, the model determines that hydropower falls from about 73% to 65% of Canadian electricity generation by 2050, while wind power increases from about 8% to 11%. Countries may be better able to achieve electrification and renewable energy targets at lower cost by avoiding large-scale, overrun-prone hydropower and nuclear generation projects. Model results support that cost overruns are important considerations for policy decisions related to electricity sector development in Canada and elsewhere. Highlights: Hydropower is included endogenously in GCAM, an integrated assessment model. Electricity generation scenarios are modelled to 2050 with cost overruns for Canada. Accounting for expected cost overruns decreases additional hydropower development. Canadian hydropower expansion could shift electricity emissions to other sectors. Adoption of renewables may not reduce Canada's emissions without electrification.